2010
DOI: 10.1007/s00425-010-1284-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a miraculin-like gene differentially expressed during coffee development and coffee leaf miner infestation

Abstract: The characterization of a coffee gene encoding a protein similar to miraculin-like proteins, which are members of the plant Kunitz serine trypsin inhibitor (STI) family of proteinase inhibitors (PIs), is described. PIs are important proteins in plant defence against insects and in the regulation of proteolysis during plant development. This gene has high identity with the Richadella dulcifica taste-modifying protein miraculin and with the tomato protein LeMir; and was named as CoMir (Coffea miraculin). Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Although characteristically expressed in fruits, the induction of miraculin-like proteins in non-fruit tissues (i.e. stems, leaves or roots) has been strongly associated with pest or pathogen attack, suggesting their involvement in defense [42, 53, 54]. Tsukuda et al [41] first characterized two distinct miraculin-like proteins in rough lemon ( Citrus jambhiri Lush), RlemMLP1 (miraculin-like protein 1) and RlemMLP2 (miraculin-like protein 2) and demonstrated the induction of RlemMLP1 and/or RlemMLP2 by microbe attack.…”
Section: Resultsmentioning
confidence: 99%
“…Although characteristically expressed in fruits, the induction of miraculin-like proteins in non-fruit tissues (i.e. stems, leaves or roots) has been strongly associated with pest or pathogen attack, suggesting their involvement in defense [42, 53, 54]. Tsukuda et al [41] first characterized two distinct miraculin-like proteins in rough lemon ( Citrus jambhiri Lush), RlemMLP1 (miraculin-like protein 1) and RlemMLP2 (miraculin-like protein 2) and demonstrated the induction of RlemMLP1 and/or RlemMLP2 by microbe attack.…”
Section: Resultsmentioning
confidence: 99%
“…In Citrus and Poncirus trifoliata , a miraculin homologue is down-regulated by cold stress (which reduces water availability) [53]. In coffee, Coffea miraculin ( CoMir ) expression was prominent during the early stages of fruit development and then repressed throughout fruit maturation [54]. Like the up-regulation of VvGolS (see above), the down-regulation of the grapevine miraculin-like gene may be a response to a decrease of water availability.…”
Section: Resultsmentioning
confidence: 99%
“…However, this gene was also upregulated in C. arabica. The trypsin inhibitor Kunitz gene is already reported in coffee by Mondego et al (2005Mondego et al ( , 2011; this is the same miraculin-like gene, CoMir. Structural protein modeling indicated that CoMir had structural similarities with the Kunitz STI proteins but suggested specific folding structures (Mondego et al 2011).…”
Section: Number Of Sequencesmentioning
confidence: 99%
“…The trypsin inhibitor Kunitz gene is already reported in coffee by Mondego et al (2005Mondego et al ( , 2011; this is the same miraculin-like gene, CoMir. Structural protein modeling indicated that CoMir had structural similarities with the Kunitz STI proteins but suggested specific folding structures (Mondego et al 2011). The gene is also upregulated after coffee leaf miner (Leucoptera coffella) oviposition in resistant plants of a progeny derived from crosses between C. racemosa (resistant) and C. arabica (susceptible) and downregulated during coffee leaf miner oviposition and larvae eclosion (herbivoria) in susceptible plants.…”
Section: Number Of Sequencesmentioning
confidence: 99%
See 1 more Smart Citation